Does lipoprotein(a) predict cardiovascular events in a long-term follow-up?. (11th May 2021) - Borges-Rosa, J; Campos, GM; Martinho, S; Almeida, JPL; Goncalves, V; Ferreira, C; Freitas, AA; Ferreira, JA; Milner, J; Oliveira-Santos, M; Baptista, R; Goncalves, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Elevated plasma lipoprotein(a) [Lp(a)] concentrations are associated with an increased risk of atherosclerotic cardiovascular disease and its role in risk categorizing was recognized in the new ESC guidelines for the management of dyslipidaemias. We investigated 1) the association between baseline Lp(a) levels and incident long-term cardiovascular (CV) events and 2) its relationship with type 2 diabetes mellitus (T2DM) in a Southern European population. Methods: We retrospectively assessed baseline Lp(a) concentrations in a total of 499 patients of a primary prevention cohort followed at the Lipidology Clinic of our hospital, with a median follow-up time of 15 (IQR 12-17) years. Lp(a) was analysed as a continuous variable, as a categorical variable with a 180mg/dL cut-off and by quartiles. We collected data on major CV events (CV death, myocardial infarction, stroke) as a composite outcome. Cox proportional hazard regression analyses were used to estimate hazard ratios (HR) and 95% confidence interval (CI). Results: Mean age was 48.30 ± 14.41 years and 61.70% were male (n = 499). Median Lp(a) was 36.60 (IQR 0-396) mg/dL and 12.4% of patients had very high Lp(a) (≥180mg/dL); T2DM prevalence was 13.60%. The composite outcome incidence was 10%. At the baseline, individuals with T2DM had lower Lp(a) levels (11.85 IQR 3-330 mg/dL vs. 46.40 IQR 0-396, p < 0.01 mg/dL). There was a moderate inverse correlation between Lp(a) and HbA1c (r = -0.67, p < 0.01) but no significant correlations with lipid profile (total, LDL or HDL), risk scores (SCORE or the ACC pooled cohort equation), age nor gender. We found no relationship between baseline Lp(a) quartiles and composite outcome's incidence (age-, sex-, and diabetes-adjusted HR: 1.15, 95%CI: 0.71-1.87, p = 0.57) (Figure 1), neither with the individual CV endpoints. Exploratory analysis showed that patients on aspirin had lower Lp(a) levels (29.55 IQR 0-264 mg/dL vs. 63.60 IQR 1-396 mg/dL, p < 0.01). Conclusion: In a single centre cohort of a primary prevention southern European population, we did not find an association between Lp(a) levels and incident CV events in a 15-year median follow-up time.